Immunological effects of radiopharmaceutical therapy - Shea, Amanda G.; Idrissou, Malick Bio; Torres, Ana Isabel; Chen, Tessa; Hernandez, Reiner; Morris, Zachary S.; Sodji, Quaovi H. (Frontiers in Nuclear Medicine, 2024)
Radiation therapy (RT) is a pillar of cancer therapy used in more than half of all cancer patients. Clinically, RT is mostly delivered as external beam radiation therapy (EBRT). However, the scope of EBRT is limited in the metastatic setting when all sites of disease need to be irradiated. Such limitation is attributed to radiation-induced toxicities including bone marrow and hematologic toxicities, ensuing from a large EBRT field. Radiopharmaceutical therapy (RPT) has emerged as an alternative to EBRT for the irradiation of all sites of metastatic disease. While RPT can reduce tumor burden, it can also impact the immune system and anti-tumor immunity. Understanding these effects is crucial for predicting and managing treatment-related hematological toxicities and optimizing their integration with other therapeutic modalities such as immunotherapies. Herein, we review the immunomodulatory effects of α-and β-particle emitter-based RPT on various immune cell lines including CD8+ and CD4+ T cells, natural killer (NK) cells, and regulatory T (Treg). We briefly discuss Auger electron-emitter (AEE) based RPT and lastly, we highlight the combination of RPT with immune checkpoint inhibitors, which may offer potential therapeutic synergies for patients with metastatic cancers.